Efforts to Increase Student Interest in Physical Fitness in Physical Education Learning at SMAN 02 Madiun - Lestari, Fitria Dwi; Kriswanto, Edi; Purnomo, Mochamad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Physical education learning is less popular with students because of students' lack of understanding of the importance of maintaining a healthy and fit body. The aim of this research is to find out students' interest before and after taking a fitness test using the Spiral Kemmis and Taggart method consisting of two cycles, each cycle using four components of action, namely planning, action, observation and reflection. The population in this study involved all classes With a percentage result of 15% in the very interested (SM) category, the interested (M) category obtained a result of 40%, the less interested (KM) category with a percentage result of 28 %, the Not Interested (TM) category obtained 10% and the very not interested category (STM) with a percentage of 6%. From the results of classroom action research, there was a significant increase between before and after the fitness test due to students' lack of understanding about physical fitness. Therefore, student interest can be increased by making learning less boring and providing students with an understanding of the importance of maintaining physical fitness and planning schedules. regular physical fitness tests to monitor the development of students' fitness levels.